2003
DOI: 10.4049/jimmunol.171.12.6344
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: A Potent Adjuvant Effect of Ligand to Receptor Activator of NF-κB Gene for Inducing Antigen-Specific CD8+ T Cell Response by DNA and Viral Vector Vaccination

Abstract: The ligand to receptor activator of NF-κB (RANK-L)/RANK interaction has been implicated in CD40 ligand/CD40-independent T cell priming by dendritic cells. In this report, we show that the coadministration of the RANK-L gene with a Trypanosoma cruzi gene markedly enhances the induction of Trypanosoma Ag-specific CD8+ T cells and improves the DNA vaccine efficacy. A similarly potent adjuvant effect of the RANK-L gene on the induction of Ag-specific CD8+ T cells was also observed when recombinant influenza virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 23 publications
3
13
2
Order By: Relevance
“…In all of these cases, the antigen used in the DNA vaccine was cell associated, i.e., located either in the cytoplasm, like ␤-galactosidase (13,60), or on the cell membrane, like HIV-1 gp160 (39) or respiratory syncytial virus envelope (31). In contrast, the present report and two previous reports failed to find any adjuvant effects with pMemCD40L-like plasmids when secreted antigens were studied (e.g., TSSA from Treponema cruzi [61] or gp120 [88]). Antigen localization has been previously identified as an important variable for DNA vaccination (12,62,69,75,89) and has implications for the selection of adjuvanting molecules.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In all of these cases, the antigen used in the DNA vaccine was cell associated, i.e., located either in the cytoplasm, like ␤-galactosidase (13,60), or on the cell membrane, like HIV-1 gp160 (39) or respiratory syncytial virus envelope (31). In contrast, the present report and two previous reports failed to find any adjuvant effects with pMemCD40L-like plasmids when secreted antigens were studied (e.g., TSSA from Treponema cruzi [61] or gp120 [88]). Antigen localization has been previously identified as an important variable for DNA vaccination (12,62,69,75,89) and has implications for the selection of adjuvanting molecules.…”
Section: Discussioncontrasting
confidence: 54%
“…3B). The addition of a plasmid for membrane CD40L (pMemCD40L) to the pScGag vaccine had no effect on these elicited responses, in contrast to several reports (13,31,39,57,60,80,96) but consistent with two recent reports on DNA vaccination (61,88). Remarkably, the plasmid for 4-trimer soluble CD40L (pSP-D-CD40L) significantly augmented the response to the pScGag DNA vaccine (Fig.…”
Section: Construction Of Expression Plasmids For 1- 2- and 4-trimercontrasting
confidence: 49%
“…We designated the "surface protein" TSSA, since its amino acid sequence was highly homologous to the T. cruzi trans-sialidase superfamily protein. Although we have not determined yet whether the TSSA actually has neuraminidase and trans-sialidase activities, we demonstrated that the DNA encoding TSSA was highly immunogenic, conferring protective immunity in C57BL/6 mice against T. cruzi infection (19,27,28,29).…”
Section: Animals and Parasite Female C57bl/6 (H-2mentioning
confidence: 99%
“…An H-2K b -restricted CD8 ϩ -T-cell epitope peptide, ANYNFTLV, derived from TSSA (19,27,28,29) (Fig. 1A) was synthesized and used for immunological assays.…”
Section: Animals and Parasite Female C57bl/6 (H-2mentioning
confidence: 99%
“…Adjuvant effects were consistently observed if the antigen was located in the cytoplasm (6,10) or on the cell membrane (7,8). However, adjuvant effects were not observed if the antigen was secreted (28)(29)(30). This becomes a limitation for HIV vaccines expressing virus-like particles (VLPs) and secreted forms of Env (important for high levels of Ab production).…”
mentioning
confidence: 99%